Налоговые льготы как инструмент стимулирования развития креативных индустрий в региональной экономике - Ольга Карпова; Ирина Тургель (Вестник Пермского университета: Серия Экономика, 2024)
Introduction. The article refers to international practices and proposes tax incentives as a stimulating mechanism for creative industries in Russia. The development of creative industries is a crucial aspect of both economic and cultural growth. However, tax support measures in Russia remain underdeveloped and inconsistent across regions.